KONSTRUKSI BUDAYA MUTU RELEVANSINYA DENGAN MANAJEMEN MUTU GURU DALAM PEMBELAJARAN PENDIDIKAN AGAMA HINDU - Anggreni, Ni Made (LPM IHDN Denpasar, 2016)
Restoring the quality of the education cannot be separated from the role of the educators. The quality here refers to the attitudes, values, norms, and system that are shared within the institution to produce quality graduates. The educators are to create the conducive atmosphere at schools, which requires competence in class managemenet. The Hindu classes teach the students to be active in order to meet the standard quality of the education therefore reach the vision and fulfill mission of the institution.